Technology of Telecommunication System in Management Information Systems - Meiryani; Siagian, Pariang; Juwita, Anita; Fitri, Yessi (International Journal of Psychosocial Rehabilitation, 2020)
The development of information and communication technology has been so fast that it affects every aspect of human life. It was realized that technology products had become a daily necessity. Television, telephone, fax, cellular phone (mobile) users and now the internet is not a strange and new thing, especially in big cities. Now it is necessary to look at how the use of the internet, whether it is going according to its original purpose, is utilized to facilitate human life, because in addition to contributing to the improvement of human welfare, progress and civilization, it is also an effective suggestion for committing crime. The progress of information and communication technology currently has the influence on the development of data transmission with the development of information technology allows the process of delivering information that is both fast and relevant.